2006
DOI: 10.1002/cphc.200600221
|View full text |Cite
|
Sign up to set email alerts
|

A Joint Theoretical–Experimental Investigation of the Faraday Effect in Benzene, Toluene, and p‐Xylene

Abstract: The linear magneto-optical effect, known as the Faraday effect, consists of the rotation of the plane of polarization of linearly polarized light when it propagates through a medium placed in a magnetic field with nonzero component in the direction of light propagation. [1][2][3][4] Far from absorption, the Faraday effect is related to the Verdet constant, [5] a quantity characteristic of the substance which depends on concentration, temperature, and frequency. Using the response formalism, [6] it is represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 29 publications
2
37
0
Order By: Relevance
“…3 are in good agreement with those reported by other groups. 21,27,28 The observed spectra clearly separated into three groups based on their magnitude: naphthalene derivatives, benzene derivatives, and aliphatic compounds. Furthermore, it was indicated that aromatic groups have an increasing effect on the FR in the visible region.…”
Section: Fr Dispersion Of Organic Liquidsmentioning
confidence: 99%
“…3 are in good agreement with those reported by other groups. 21,27,28 The observed spectra clearly separated into three groups based on their magnitude: naphthalene derivatives, benzene derivatives, and aliphatic compounds. Furthermore, it was indicated that aromatic groups have an increasing effect on the FR in the visible region.…”
Section: Fr Dispersion Of Organic Liquidsmentioning
confidence: 99%
“…The Verdet constant, measured in rad normalT1normalm1 within the Système International (SI) of units, is a scalar, obtained by spatial averaging from a third‐rank axial tensor scriptVαβγ, referred to as Verdet tensor, also taken into account to rationalize the inverse Faraday effect, in which optical magnetization is induced by applying circularly polarized light …”
Section: Translation Of Frequency‐dependent Response Tensorsmentioning
confidence: 99%
“…The Verdet constant, measured in rad T −1 m −1 within the Système International (SI) of units, is a scalar [2][3][4][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33], obtained by spatial averaging from a third-rank axial tensor V αβγ , hereafter referred to as Verdet tensor, also taken into account to rationalise the inverse Faraday effect, in which optical magnetisation is induced by applying circularly polarised light [34,35]. A tensor with analogous properties has been considered to predict nuclear magnetic resonance (NMR) chemical shift induced by a circularly polarised laser beam [35][36][37].…”
Section: Introductionmentioning
confidence: 99%